Cross-Cultural Adaptation and Validation of the Emotional Inhibition Scale in a Chinese Cancer Sample - Liu, Liping; Xu, Yikai; Wu, Yanni; Li, Xiaoxia; Zhou, Chunlan (Frontiers in Psychology, 2021)
The Emotional Inhibition Scale (EIS) is a brief measure of the four-factor model with documented validity in mood-disorder samples and could be useful for assessing emotional inhibition in patient populations such as individuals with cancer. The aim of this study was to adapte EIS to Chinese conditions and examine the psychometric characteristics of the EIS in cancer patients. Recruited samples were involved into two phase process (sample 1, n=100, and sample 2, n=202). A sample of 100 (sample 1) and a sample of 202 (sample 2) with cancer completed a survey including the EIS. And the Toronto Alexithymia scale-20 were completed in 2 samples to assess criterion validity. Statistics analyses included internal consistency (samples 1), explorary factor analyses (EFAs; samples 1) confirmatory factor analyses (CFAs; samples 2). Results showed that EFA and CFA confirmed the four-factor solution proposed by the original authors ( verbal inhibition, self-control, disguise of feelings and timidity ). Support was found that the internal consistency and test-retest reliability of the EIS are satifactory. In conclusion, the EIS demonstrated acceptable reliability and validity for assessing emoional inhibition among cancer patients in China and could be a useful measure to assess the level of emotional inhibition and the effect of emotional disclosure intervention.